GCC’s Post-Oil Transition: Rising Profitability Advantage of Non-Energy Sectors - Zehri, Chokri; Alharithi, Mohammed (International Journal of Energy Economics and Policy, 2025)
We examine the asymmetric effects of national economic diversification policies on firm-level profitability in the Gulf Cooperation Council (GCC), addressing a critical gap in the microeconomic literature on the region’s transition from hydrocarbons. Using a dynamic panel dataset of 444 firms across all six GCC countries from 2012 to 2024, we employ a Difference-in-Differences (DiD) approach complemented by System Generalized Method of Moments estimation to establish causal relationships while rigorously addressing endogeneity concerns. The results reveal that diversification policies significantly boosted profitability in non-oil firms, with policy milestones increasing asset-based returns by 1.8% and equity-based returns by 2.5%, while government subsidies amplified these effects by an additional 4.2% and 6.2%, respectively. These impacts intensified post-2019, with targeted subsidies driving profitability gains of 8.2% on assets and 12.3% on equity. Conversely, oil-dependent firms showed no statistically significant response to policy interventions. The findings underscore the efficacy of targeted fiscal incentives and selective policy support in driving successful economic diversification, offering valuable insights for policymakers in resource-rich economies seeking to engineer sustainable post-oil transitions through precise firm-level interventions.